2020
DOI: 10.3390/brainsci10110871
|View full text |Cite
|
Sign up to set email alerts
|

Visual-Attentional Load Unveils Slowed Processing Speed in Multiple Sclerosis Patients: A Pilot Study with a Tablet-Based Videogame

Abstract: Slowing in information processing speed (IPS) is the key cognitive deficit in multiple sclerosis (MS). Testing IPS in different cognitive load conditions by using computerized tools might reveal initial IPS slowness underestimated by classic paper-and-pencil tests. To investigate the extent to which IPS can be affected by increased task demands, we developed three tasks based on the manipulation of the visual-attentional load, delivered with a home-made, tablet-based videogame. Fifty-one patients with MS (pwMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The results highlighted a strong positive and significant association with respect to the MEC-35 scale (Spearman rho=0.71) according to Cohen [24]. This results aligns with other works, like the study of Pitteri et al [14], who also found significant correlations between the SDMT and the accuracy response of their task, thus verifying its validity as a diagnostic tool. Similarly, Kalafatis et al [16] demonstrated a convergent validity with the MOCA test (Pearson r = 0.58) and the ACE test (Pearson r = 0.62), respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results highlighted a strong positive and significant association with respect to the MEC-35 scale (Spearman rho=0.71) according to Cohen [24]. This results aligns with other works, like the study of Pitteri et al [14], who also found significant correlations between the SDMT and the accuracy response of their task, thus verifying its validity as a diagnostic tool. Similarly, Kalafatis et al [16] demonstrated a convergent validity with the MOCA test (Pearson r = 0.58) and the ACE test (Pearson r = 0.62), respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have used classical tests as the basis for the design of new proposals to be compared. Pitteri et al [14] presented a video game that sought to identify whether there was a cognitive impairment in the information processing speed (IPS). The results revealed that those patients with multiple sclerosis (MP) showed a lower performance compared to healthy ones.…”
Section: Introductionmentioning
confidence: 99%
“…23 The evidence of interactive video game therapeutic exercises for improving balance and motor functions in PwMS were inconclusive, even if few studies showed a possible positive effect on balance and cognitive functions such as processing speed. [24][25][26][27] Furthermore, patients' motivation seems to be capable of being increased during active video game rehabilitation, allowing patients to exercise more consistently. 22 All previous studies did not investigate the effects on motor and cognitive functions simultaneously, particularly when compared with conventional instrumental balance training.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%